A case report of a rare intrahepatic cholangiocarcinoma with rectal metastasis - Jiang, Shu-min; Huang, Lu; Jiang, Quan (Frontiers in Oncology, 2025)
Intrahepatic cholangiocarcinoma (ICC) is a primary liver cancer with insidious onset, rapid progression, and poor prognosis. The lymphatic system is the main route of ICC distant metastasis, with lungs, adrenal glands, and brain as the most common extrahepatic sites. However, extrahepatic metastases of ICC have rarely been reported in patients with rectal symptoms as initial symptoms, and the diagnosis relies on the specific immunohistochemical features of intestinal lesion biopsy. Herein, this study presents an incidental case of ICC with rectal metastasis to investigate its characteristics based on its diagnosis, metastasis, and treatment.